Simulation of strain fields in GaSb/InAs heteroepitaxial system - Shutov, S.V.; Baganov, Ye.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Mechanical strains taking place in GaSb/InAs heterosystem in the presence of misfit dislocation network are investigated. Distributions of energy of strains and deformations in the system with misfit dislocation network were found using two-dimensional simulation. The radius of the dislocation core, depths of the strain penetration into the substrate and epitaxial layer as well as change of the material bandgaps near the heterointerface were calculated.